KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN ETOS KERJA GURU PADA MTs PONDOK BESAR ROUDLOTUL MUBTADIIN BALEKAMBANG NALUMSARI JEPARA TAHUN PELAJARAN 2017/2018 - Abdur Rouf (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
The purpose of this research is: 1) to analize the leadership of the madrasa principals at MTs Pondok Besar Roudlotul Mubtadiin Balekambang MTs, 2) to find out the work ethic of teachers at MTs Pondok Besar Roudlotul Mubtadiin Balekambang MTs, and 3) to find out the supporting and inhibiting factors of the teacher's work ethic at Pondok MTs Pondok Besar Roudlotul Mubtadiin alekambang. This study is a kind of qualitative research field research. Research instrument using observation guide and interview guide. Processing and data analysis techniques are carried out through three stages, namely data reduction, data presentation, and conclusion and data verification. The results showed that 1) the leadership of MTs Pondok Besar Roudlotul Mubtadiin Balekambang is quite good because it upholds responsibility with trustworthy, 2) The work ethic of teachers at the Pondok Indah Roudlotul Mubtadiin Balekambang MTs is categorized as good, because they have shown performance and various kinds of efforts undertaken for achievement of learning objectives, 3) Factors supporting work ethic (discipline, personality of the teacher carrying out the duties, exemplary and firmness of the principal. Obstacle Factors, there are still many teachers who teach as usual, namely lecture methods, so that students' interest in learning is seriously reduced. Keywords. Leadership, Head of Madrasah, Work Ethic, Teacher